Area And Diversity Of A Crop Reflects The Diversity Of Others - Joshi, Bal Krishna; Upadhyay, Madhusudan Prasad; Baniya, Bimal Kumar; Gauchan, Devendra (Journal of Agriculture and Environment, 2013)
This study was carried out to relate the diversity of one crop in terms of number of landraces and farm area with the diversity of other crop. Information collected during baseline survey of in-situ global project (1999) on three crops namely rice, finger millet and sponge gourd in Jumla, Kaski and Bara of Nepal were used. Farm area of each variety and number of landraces grown by sampled household were used for F-test, regression and chi-square analyses to test the diversity of one crop with respect to other. Households having large number of landraces of finger millet maintained large number of rice landraces. Households maintaining different landraces of sponge gourd and finger millet showed a relation with their farm area allotted to rice landraces. Households having large area for rice cultivation maintained a large number of rice landraces in all the sites. The analyses showed that the farmers growing diversity in one crop are more likely to grow diversity in other crops. Similarly, if area in a household allotted to a particular crop species is large, there is chance of growing high diversity of the crop species. Households having large farm size and maintaining high diversity of a crop species may be target farmers for genetic resources management. The Journal of Agriculture and Environment Vol:13, Jun.2012, Page 5-8 DOI: http://dx.doi.org/10.3126/aej.v13i0.7581